Economic security of the country for stable development - Гарькава, Вікторія Федорівна; Гарькава, В. Ф.; Гарькава, Виктория Федоровна; Harkava, Viktoriia F.; Кібік, Ольга Миколаївна; Кібік, О. М.; Кибик, Ольга Николаевна; Kibik, Olha M.; Титок, Вікторія Вікторівна; Титок, В. В.; Титок, Виктория Викторовна; Tytok, Viktoriia V.; et al. (Magnanimitas Assn., 2021)
The slowdown in EU economic growth leads to the search for ways to ensure security in the economic sphere, in particular through a strategic partnership with world leaders. The aim of this article was to identify the state of economic security of EU countries in the context of stable development. The research methodology is based on the correlation and factor analysis of the factors that determine the state of economic security based on the system of indicators of stable development of the EU countries for 2011-2020. The results show a slowdown in economic growth in the EU in 2011-2020, in particular the systemic nature of the crisis. The factor analysis suggests that long-term unemployment, changes in export and import indices best explain the variation in EU GDP growth.

Уповільнення економічного зростання ЄС призводить до пошуку шляхів забезпечення безпеки в економічній сфері, зокрема через стратегічне партнерство зі світовими лідерами. Метою даної статті було виявлення стану економічної безпеки країн ЄС у контексті стабільного розвитку. Методологія дослідження базується на кореляційному та факторному аналізі чинників, що визначають стан економічної безпеки, на основі системи показників стабільного розвитку країн ЄС на 2011-2020 роки. Результати свідчать про уповільнення економічного зростання в ЄС у 2011-2020 роках, зокрема системний характер кризи. Факторний аналіз показує, що тривале безробіття, зміни в експортних та імпортних індексах найкраще пояснюють різницю зростання ВВП ЄС.
Harkava V. Economic security of the country for stable development / V. Harkava, O. Kibik, V. Tytok et al. // AD ALTA: Journal of Interdisciplinary Research. - Vol. 11. - Iss. 2. - Magnanimitas Assn., 2021. - Р. 138-142.
Keywords: economic security; EU security; GDP growth; stable development; strategic partnership; економічна безпека; безпека ЄС; зростання ВВП; стабільний розвиток; стратегічне партнерство; Research Subject Categories::SOCIAL SCIENCES::Business and economics::Economics